Social representations of the family caregiver about palliative care in terminal patient / Representações sociais do cuidador familiar sobre cuidados paliativos em paciente terminal - da Silva, Silvio Éder Dias (2024)
Objective: to analyze the social representations of family caregivers about palliative care in patients with serious, progressive disease that threatens the continuity of their lives. Method: the study was descriptive, using a qualitative approach. For the interpretation of the results, the Theory of Social Representations, created by Serge Moscovici and Denise Jodelet, was used as a theoretical contribution. The research was carried out with 30 family caregivers of patients with end-of-life cancer. Data collection was carried out through semi-structured interviews and the thematic analysis technique. Results: after analyzing the data, three categories emerged: common sense and cancer; palliative care, the patient and caregivers and caregivers and their social representation. Final considerations: the social representations of the family caregiver made it possible to identify the true extent of daily issues in the professional routine.